Pengaruh Biaya Produksi Dan Harga Pokok Produksi Terhadap Harga Jual Usaha Mikro Kecil Menengah Kecamatan Padang Utara - Susri Andari; Febryandhie Ananda (UNIVERSITAS MARITIM AMNI SEMARANG, 2023)
The selling price is an attempt to balance the desire to get maximum profit from a large increase in sales and a decrease in sales volume when the selling price charged to consumers is too expensive. This study aims to determine the effect of Production Costs and Production Costs on Selling Prices of Micro, Small and Medium Enterprises in North Padang District. Source of data used in this research is primary data. In using primary data when processing data, the data is found directly by circulating a list of statements (questionnaire). The population of this study is based on data from Padang city SMEs in 2021, namely the North Padang sub-district. The number of samples used in the study were 60 respondents. The analytical method used is multiple regression analysis. Based on the test results, it was found that Production Costs had a positive and significant effect on the Selling Price of Micro, Small and Medium Enterprises in North Padang District, and the Cost of Production had no effect on the Selling Price of Micro, Small and Medium Enterprises in North Padang District.